008 Comparison of weight-based vs estimated contrast dose techniques in coronary computed tomography angiography. (5th May 2016) - Loughborough, Will; Manghat, Nathan; Hamilton, Mark
Abstract : Introduction: The purpose of this study was to compare weight based versus estimated contrast dosing techniques in coronary computed tomography angiography (CCTA). Methods: This single centre retrospective observational study compared 47 patients undergoing CCTA. All imaging was performed on a 320 slice scanner at 100kV with bolus tracking. In the weight based protocol, patients received 22mg/kg/s of contrast for 14 s. In the estimated group, contrast dosing and rate was estimated by a consultant cardiac radiologist. Two tailed t tests determined significance between patient and contrast variables. Enhancement of cardiac chambers and coronary arteries was calculated through region of interest areas in Hounsfield units (HUs). Results: There were no significant differences between the groups in terms of mean weight (p = 0.42) or mean heart rate (p = 0.29). The estimated group received a significantly higher volume of contrast than the weight based group (71mls vs 58mls, p= <0.001). There was a non-significant difference between groups in MEV of coronaries. Both groups produced diagnostic MEVs above 400 HUs. Right sided chambers were attenuated significantly more in the best guess than the weight based group, for example right ventricle MEV 279 vs 141 (p = 0.01). SDs in coronary arteries were similar between groups but weight based contrast protocol achieved lower standard deviation of HUs on the right sided chambers. Conclusion: Weight based and estimated contrast regimes produce similar variability and adequate opacification in coronary arteries in CCTA. However, weight adjusted contrast dosing technique administers a lower dose of contrast, with lower enhancement of the right sided chambers.